The Relationship Between Sleep Hygiene Behavior And Sleep Quality In Male Adolescents At Mbs Al Amin Bojonegoro Middle School Based On Dorothea E Orem's Theory - Fanny Felly Gita Fanny Felly Gita; Sri Mulyani; Siti Patonah; Fidrotin Azizah (International Journal of Health Engineering and Technology, 2026)
Adolescence is a period that is vulnerable to sleep quality disorders due to busy activities and less than optimal sleep hygiene implementation, especially in Islamic boarding school environments. This study aims to analyze the relationship between sleep hygiene behavior and sleep quality in male adolescents at SMP MBS Al Amin Bojonegoro based on Dorothea E. Orem's Self-Care Deficit theory. This study used a quantitative correlational analytic design with a cross-sectional approach. The study population was 66 students in grades VIII and IX, with a sample of 57 respondents selected using a simple random sampling technique. The research instrument used a sleep hygiene questionnaire and the Pittsburgh Sleep Quality Index (PSQI). Data analysis was carried out univariately and bivariately using the Spearman correlation test. The results showed that 52.6% of respondents had poor sleep hygiene behavior and 56.1% had poor sleep quality. Spearman analysis showed a significant relationship between sleep hygiene behavior and sleep quality (p = 0.000) with a strong correlation strength (r = 0.769). This study concludes that better sleep hygiene implementation is associated with better sleep quality, so strengthening self-care behavior needs to be optimized to improve the sleep quality of adolescents in Islamic boarding school environments.